Tuning the Rigidity of Silk Fibroin for the Transfer of Highly Stretchable Electronics. (20th April 2020) - Huang, Jun; Wang, Liu; Jin, Yuming; Lu, Peng; Wang, Lin‐Lin; Bai, Ningning; Li, Gang; Zhu, Pang; Wang, Yan; Zhang, Jianming; Wu, Zhigang; Guo, Chuan Fei
Abstract: The transfer of stretchable electrodes or devices from one substrate to another thin elastomer is challenging as the elastic stamp often yields a huge strain beyond the stretchability limit of the electrodes at the debonded interface. This will not happen if the stamp is rigid. However, a rigid material cannot be used as the substrate for stretchable electrodes. Herein, silk fibroin with tunable rigidity (Young's modulus can be changed from 134 kPa to 1.84 GPa by controlling the relative humidity) is used to transfer highly stretchable metal networks as highly conformable epidermal electrodes. The silk fibroin stamp is tuned to be rigid during peeling, and then be soft and highly stretchable as a substrate when laminated on moisturized human skin. In addition, the epidermal electrodes exhibit no skin irritation or inflammation after attaching for over 10 d. The high compliance results in a lower interface impedance and lower noises of the electrode in measuring electromyographic signals, compared with commercial Ag‐AgCl gel electrodes. The strategy of tuning the rigidity at different stages of transfer is a general method that can be extended to the transfer of other stretchable electrodes and devices for epidermal electronics, human machine interfaces, and soft robotics. Abstract : The transfer of stretchable and ultrathin electronics is challenging because peeling a stamp that is soft from a donor substrate imposes a large strain in the debonded interface, causing failure of the electronics. This issue can be addressed by using a silk fibroin substrate, which is tuned to be rigid during transfer but soft when used for applications.